2006
DOI: 10.1097/01.wnr.0000221835.26093.5e
|View full text |Cite
|
Sign up to set email alerts
|

Gesture handedness predicts asymmetry in the chimpanzee inferior frontal gyrus

Abstract: Neuroanatomical asymmetries have been identified in chimpanzee frontal and temporal lobes including regions believed to be homologous to human Broca's and Wernicke's areas. This study examined whether or not neuroanatomical asymmetries in chimpanzees are associated with hand use during gestural communication. Analyses revealed that those chimpanzees that reliably employ their right hand for manual gestures have larger inferior frontal gyri in the left hemisphere than those apes that do not show consistent hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
52
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 23 publications
11
52
1
Order By: Relevance
“…The association between hand preferences for throwing and asymmetries within the IFG and KNOB are also consistent with previous studies showing that handedness for other forms of tool use, such as simulated termite-fishing and nutcracking, is linked to lateralization in the cortical language area homologues of chimpanzees [33,44]. It should also be noted that asymmetries in hand use for manual gestures are associated with asymmetries within the IFG [45] Thus, the results reported here are consistent with the evolutionary hypothesis that throwing may have served as a preadaptation for the neural adaptation of motor programmes necessary for complex motor actions, including language and speech [11].…”
Section: Discussionsupporting
confidence: 91%
“…The association between hand preferences for throwing and asymmetries within the IFG and KNOB are also consistent with previous studies showing that handedness for other forms of tool use, such as simulated termite-fishing and nutcracking, is linked to lateralization in the cortical language area homologues of chimpanzees [33,44]. It should also be noted that asymmetries in hand use for manual gestures are associated with asymmetries within the IFG [45] Thus, the results reported here are consistent with the evolutionary hypothesis that throwing may have served as a preadaptation for the neural adaptation of motor programmes necessary for complex motor actions, including language and speech [11].…”
Section: Discussionsupporting
confidence: 91%
“…These neuroanatomical correlates of an auditory communicative gesture are congruent with previous studies in chimpanzees showing that hand preference for human-directed food-begging gestures predicts variation of the neuroanatomical asymmetry in the IFG [66] and of the grey matter asymmetries in the PT [67]. In contrast, it has been previously reported that handedness for non-communicative motor actions (bimanual coordinated task and unimanual reaching) does not significantly correlate with the IFG and PT homologues [66,80]. Thus, these findings support the notion that the gestural communication system in chimpanzees might involve a common cerebral substrate with human language and could have been the precursor of the cerebral substrate for language in the common ancestor of humans and chimpanzees at least 5-7 Myr ago.…”
Section: Discussionsupporting
confidence: 89%
“…The full details of the procedure of image collection are provided in the electronic supplementary material (point 1; see also [66]). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations